Strike Settlement and Economic Activity : An Empirical Analysis - Swidinsky, Robert (Relations industrielles / Industrial Relations, 1976)
This paper explores the relationship between the outcome of strike and the level of economic activity. The findings are based on Canadian data for the period 1901-1953.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z